The impact of peer assessment on the attainment level of oral presentations skills - lvalue lvalue; Bojan Prosenjak; Iva Lučev (Universitat Jaume I. Department of English Studies, 2020)
Bojan Prosenjak LABOS language training and translations, Croatia Iva Lučev Libertas International University, Croatia   ABSTRACT The aim of contemporary language for specific purposes (LSP) is to prepare students for independent and competent performance in the globalised world of English as a lingua franca, with oral presentations as an indispensable element. Recognising that many students experience anxiety when faced with public speaking, instructors need to boost their self-confidence and improve their oral presentation skills, which can be achieved by promoting team-work and collaborative learning. The aim of this paper is to explore whether peer assessment of oral presentations influences the level of students' attainment of oral presentation skills. The research was conducted at the Dag Hammarskjöld University College of International Relations and Diplomacy in Zagreb. By using an assessment tool, the participants evaluated their colleagues' presentations at the beginning and the end of the semester. A significant difference between the two sets of results was found. Additionally, the analysis of students' attitudes toward peer assessment complements the quantitative findings, demonstrating that participants recognise its importance and are able to self-reflect more efficiently on their own and their colleagues' work.